Development of a new fatigability jumping protocol: Effect of the test duration on reproducibility and performance - Paulus, J.; Croisier, J.-L.; Kauxa, J.-F.; Tubez, F.; Meyer, D.; Schwartz, C. (Science & Sports, 2021)
The Wingate Anaerobic Test (WAnT) and isokinetic fatigability protocols are mainly used to evaluate the anaerobic power of athletes for whom jumping is a predominant action in their sport. Nevertheless, the testing protocol must be as close as possible to the activity pattern of the sport to be valid. Therefore, for these athletes, the test should consist of repetitions of jumps that are task-specific. Our aim was to propose a new jumping protocol allowing for specific assessment of fatigue, to examine its absolute and relative reliability and to determine its ideal duration. Twenty male volleyball performed fifty countermovement jumps (CMJ) at a rate of 33 jumps per minute on two occasions, with seven days recovery between each session. Jump height was computed for each CMJ using a 3D optoelectronic system, which was subsequently added to determine cumulative performance after 10, 15, 20, 25, 30, 35, 40, 45 and 50 repetitions. Reliability of the average jump height was not affected by the lengthening of the protocol and was high for all considered durations (ICC > 0.94; SEM < 5%). A decrease in performance was directly and proportionally related to the duration of the fatigability protocol. Measuring average jump height during a protocol involving 25 CMJ at the rate of 33 jumps per minute appears to represent the best compromise between reliability, induced fatigue and physiological considerations. Moreover, until 25 repetitions, the partial sums by five repetitions can and should be used to further explore the subject's performance during the test.